Hubungan Pengetahuan Remaja Putri Dengan Tingkat Kecemasan Remaja Putri Terhadap Menarche Pada Siswi MTs Miftahul Ulum Di Desa Gugul Kecamatan Tlanakan Kabupaten Pamekasan - Teguh Achmalona; Tety Ripursari; Emi Yunita (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2022)
Adolescence is one of the stages in human life which is often referred to as puberty, which is a period of transition from children to adulthood. At this stage, adolescents will experience physical, emotional and social changes as a feature of puberty. This researcher aims to analyze the relationship between adolescent knowledge and the level of anxiety of adolescent girls about menarche.The research design used a correlation analytic design, with a Cross Sectional approach. With the independent variable is the knowledge of adolescents, while the dependent variable is the level of anxiety of young women about menarche. The sample studied was 30 female students. By taking samples using Non Probability Sampling, namely the total sampling technique. Data collection using Questionnaires and Checklists. The data is presented in tabular form, narration and cross tabulation is performed. The results showed that the knowledge of adolescents was sufficient as many as 26 people (86.6%). The level of anxiety of young women about menarche with a mild level of anxiety as many as 24 people (80%). The results of the statistical test obtained a significance result of P 0.000 <a 0.05, then H0 was rejected and H1 was accepted. So it can be concluded that there is a relationship between adolescent knowledge and the level of anxiety of adolescent girls about menarche.With the problem of menarche, it is necessary to strive for problem solving between related parties, namely institutions, health service agencies, health centers by providing counseling so that risk factors can be identified and handled early.